2010
DOI: 10.4137/ehi.s5540
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study of the Clinical Hypoglycemic Effects of Allium cepa (Red Onion) in Type 1 and Type 2 Diabetic patients

Abstract: Background:Diabetes mellitus is a heterogeneous group of disorders characterized by abnormalities of carbohydrate, protein and lipid metabolism. Type 1 diabetes mellitus is an autoimmune disease caused by destruction of pancreatic beta cells and characterized by defect in insulin secretion while type 2 diabetes mellitus results from abnormalities in insulin secretion and/or insulin action or both.Objectives:The present study was conducted to investigate the clinical hypoglycemic effects of Allium cepa in type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
48
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 12 publications
(16 reference statements)
4
48
0
2
Order By: Relevance
“…It was also able to attenuate (37%) rise in plasma glucose 2 h after glucose ingestion (Myint et al, 2009). More recently, it was shown that intake of 100 g A. cepa can decrease FBG level and improve glucose tolerance test (GTT) in both T1D and T2D patients (Eldin et al, 2010). …”
mentioning
confidence: 99%
“…It was also able to attenuate (37%) rise in plasma glucose 2 h after glucose ingestion (Myint et al, 2009). More recently, it was shown that intake of 100 g A. cepa can decrease FBG level and improve glucose tolerance test (GTT) in both T1D and T2D patients (Eldin et al, 2010). …”
mentioning
confidence: 99%
“…Several studies have also reported antidiabetic activity of onion when ingested as oils or extracts (Jung, Lim, Moon, Kim, & Kwon, 2011;Matsunaga et al, 2014;Taj Eldin, Ahmed, & Elwahab, 2010). One mechanism described in literature is the inhibition of carbohydrate-digestive enzymes by onion-extracts and flavonoids thereof that is accompanied by a diminished increase in postprandial blood glucose levels (Kang et al, 2010;Kim, Jo, Kwon, & Hwang, 2011).…”
Section: Introductionmentioning
confidence: 96%
“…The antidiabetic effect of A. cepa L. (Liliaceae) was evaluated in both animal models and human subjects (Taj Eldin et al, 2010). Furthermore, the role of nutritional factors in reproduction and subfertility is important.…”
Section: Allium Cepa (Alliaceae)mentioning
confidence: 99%